A 3-month-old child with COVID-19: A case report. Issue 23 (5th June 2020) - Li, Chenxi; Luo, Fan; Wu, Bing
Abstract: Introduction: Coronavirus disease 2019 (COVID-19) is pandemic and is a medical issue. However, children account for a small portion of those with the disease, and there are few published reports of COVID-19 in children. The patient reported in this case report is the youngest case reported in Chengdu, China to date. Patient concerns: A 3-month-old male infant presented with cough and rhinorrhea. Diagnosis: Family members from Wuhan, the epicenter of the epidemic came to stay in the patient's home 16 days before the onset of his disease, and his mother had been diagnosed with COVID-19. He was diagnosed with COVID-19 based on a history of exposure and severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), detected using reverse transcription polymerase chain reaction (RT-PCR). Interventions: The patient was admitted to hospital and treated symptomatically with oral medication. Outcomes: The patient recovered completely and was discharged after one month of hospitalization. He tested negative for SARS-CoV-2 using RT-PCR and a chest CT performed 4 weeks after admission showed marked improvement prior to discharge. Conclusion: Clinicians must be aware of the presentation of COVID-19 in children because it differs from that in adults.